Methane generation from POME by using ultrasonic treatment: article - Ahmad, Mohamad Hafiz; Musa, Mohibah; Jaapar, Jefri (2017)
Production of palm oil is continue expanding these days and palm oil mill effluent (POME) is the wastewater which is generated during the production process. Among the waste generated, palm oil mill effluent (POME) is the most harmful to environment if direct discharge without treated in right way. Greenhouse gasses emitted from Palm Oil Mill Effluent anaerobic treatment pond such as methane and carbon dioxide exerted greenhouse effect to the earth. The capturing of methane gas will save the environment. This study mainly focused on methane production (CH4) from palm oil mill effluent (POME) by using Ultrasonic treatment and how much COD removal after sonification. Design of ultrasonic chamber was applied in order to design experimental work which was 1 L volume chamber with ultrasonic . The parameters of ultrasonic such as COD, pH, distance of ultrasonic from water surface were studied. Ultrasonic was operated under ambient temperature within the range ~30 to 35 ˚C. POME was treated with ultrasonic in 5 minutes by variable ratio of dilution of POME with water. POME also treated with ultrasonic with using variable distance of tip of ultrasonic from water surface. COD analysis on sample of POME before and after treatment of ultrasonic was examined to calculate percentage COD removal. The amount of methane gas obtained was about 1230 ppm . The COD content can be reduced up to 91 % reduction from the original by complete treatment.